Industrial coloration of plastics : pigments, dyestuffs, fillers, and nanomaterials - Etzrodt, Gunter (Hanser Publications, 2022)
Successful coloration of plastics is a challenging exercise, requiring deep understanding of chemical, physical, and technological factors, as well as national and international regulations. Customer and regulatory demands are often very high, concerning toxicity, environmental factors, color specification/matching, stability, and cost, among others. This book enables the reader to identify the right color preparation for a particular product application, accounting for material and design.